European constitutionalism - Tuori, Kaarlo <<[VerfasserIn]>> (Cambridge University Press, 2015)
European Constitutionalism redraws the perimeters in the debate on the nature of the European constitution. Offering a fresh approach to both doctrinal and theoretical issues, this book discusses general characteristics of the European constitution under the headings of relationality, perspectivism and discursiveness, and contains forays to sectoral constitutionalization in the micro- and macroeconomic, social and security dimensions. European constitutionalism must be examined in its interaction with Member State constitutionalism, which plays an essential role in channelling democratic legitimacy to the EU. Written by a leading expert in the field, this book will be of great interest to students and scholars alike